Development experience of Mauritius: size, growth policies and vulnerability - Luchman, Raj T. ([s.n.] [S.l.], 1991)
Examines the policies which have prompted growth and evaluates whether size has been beneficial or a constraint to growth. Addresses the issue of vulnerability as a consequence of size and policy options open to a small island country.